The Impact of Service Quality, Price Perception, and Brand Image on Customer Satisfaction among Users of Grab Online Motorcycle Taxi Services: A Case Study of Grab Customers in Yogyakarta - Marau, Viktor Erniko; Gesmani, Riko; Kaloeti, Ade Kristianus (EQUILIBRIUM - Jurnal Bisnis dan Akuntansi, 2022)
This study aims to examine the impact of service quality, price perception, and brand image on customer satisfaction among users of Grab's online motorcycle taxi services in Yogyakarta. Additionally, it seeks to identify the most dominant factor influencing customer satisfaction in this context. The research was conducted in the city of Yogyakarta, utilizing field data collection and analyzed through multiple regression analysis. A total of 100 respondents were sampled using purposive sampling methods. The findings indicate that the variables of service quality, price perception, and brand image positively affect customer satisfaction for Grab's online motorcycle taxi services in Yogyakarta. Among these factors, brand image emerged as the most significant influencer of customer satisfaction. The coefficient of determination in this study is 0.782, indicating that service quality, price perception, and brand image account for 78.2 percent of customer satisfaction, while the remaining 21.8 percent is attributed to other variables not included in this research model.